Draft Annual Plan 1970-71 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1969)
The economy of the State being based primarily on agriculture, the opportunity of employment to the educated youth of the State are limited. The expansion in the secondary and tertiary sectors has not been fast enough to employ the additional labour force, specially belonging to the educated category, with the result that unemployment in the State continues to grow in spite of 19 years of planning.
Government of Uttar Pradesh, Planning Department